Production of lactic acid from fermentation of pretreated cassava starch and leaves using Rhizopus sp - Yusuf, Nurlisa; Azmi, Azlin Suhaida; Jimat, Dzun Noraini (2012)
The potential of cassava starch and its leaves for lactic acid production was investigated using fungal Rhizopus sp. in fermentation process. The minerals content such as Zinc, Ferum and Magnesium and cyanide content in cassava leaves were investigated. The results showed that cassava leaves contain 0.12 mg/L Zn, 0.3 mg/L Fe and 2.64 mg/L Mg and no cyanogenic glycoside in leaf after dried in oven at 80ºC for 24 hours. For the optimization of hydrolysis process, three factors such as acid and starch concentrations and temperature were investigated. The maximum result of a hydrolysis process was 26.58 g/L glucose concentration obtained from Run 2 which was utilizing 25 g/L of starch and 0.20 M of HNO3 at 160ºC. Next, the fermentation process was conducted in shake flask to determine the best condition for lactic acid production. There were three different conditions affecting the concentration of lactic acid production such as inoculum dilution, temperature and agitation. The maximum lactic acid concentration of 24.61 g/L were determined from Run 2 at temperature of 30ºC using 25 ml inoculum dilution and agitated at 200 rpm. Besides, the maximum ethanol concentration was 13.49 g/L at Run 4 which was conducted at the same temperature as Run 2 but at different agitation speed (250 rpm) at pH 7. Design Expert software v6.0.8 was used to design the experiment for reducing the run of the experiment during hydrolysis and fermentation analysis using Taguchi's method by selecting the significant parameters. All results have been analyzed by High Performance Liquid Chromatography (HPLC) using the refractive index detector.